Advanced Materials for Use in Soft Self‐Healing Devices. Issue 19 (23rd February 2017) - Huynh, Tan‐Phat; Sonar, Prashant; Haick, Hossam
Abstract : Devices integrated with self‐healing ability can benefit from long‐term use as well as enhanced reliability, maintenance and durability. This progress report reviews the developments in the field of self‐healing polymers/composites and wearable devices thereof. One part of the progress report presents and discusses several aspects of the self‐healing materials chemistry (from non‐covalent to reversible covalent‐based mechanisms), as well as the required main approaches used for functionalizing the composites to enhance their electrical conductivity, magnetic, dielectric, electroactive and/or photoactive properties. The second and complementary part of the progress report links the self‐healing materials with partially or fully self‐healing device technologies, including wearable sensors, supercapacitors, solar cells and fabrics. Some of the strong and weak points in the development of each self‐healing device are clearly highlighted and criticized, respectively. Several ideas regarding further improvement of soft self‐healing devices are proposed. Abstract : Wearable devices that can negate the detrimental effects of scratched and/or mechanical cuts, and that restore the mechanical/electrical/chemical properties by a self‐healing mechanism are reviewed and discussed. The materials chemistry of self‐healing polymers/composites is reviewed and their use in/as wearable sensors, supercapacitors, and solar cells is discussed.